OVERVIEW OF NURSES IN THE PREVENTION AND CONTROL OF HEALTHCARE ASSOCIATED INFECTIONS (HAIS) AT KARDINAH - Nurcholis Nurcholis; Gayuh Siska Laksanano; Hudinoto Eko Yudyarto; Agus Mulyadi (Prodi D3 Keperawatan Tegal Poltekkes Kemenkes Semarang, 2021)
Background Nurses are most often in contact with patients, so that of all health workers, nurses are the most at risk of being exposed to various diseases. Objective: To identify the description of nurses in the prevention and control of health care associated infections (HAIs) in the emergency department of Kardinah Hospital, Tegal City. Methods: This research is a quantitative research using descriptive research methods. The sampling technique in this study used a total sampling of 40 Results: Data analysis showed that 90% of the emergency room and ICU nurses had high knowledge of the use of PPE, as many as 10% of nurses had a negative attitude in the use of PPE. The most reason for using PPE is to maintain personal safety and the most reason for not using PPE is because they are not used to it Conclusions and Suggestions: PPI provides socialization and information on the use of PPE according to hospital SOPs. IPCN is expected to be the right role model in the use of PPE, hospital management provides support and motivation to nurses to be more disciplined in the use of PPE to prevent HAIs.